Diaminopyrene modified reduced graphene oxide as a novel electrode material for excellent performance supercapacitors. Issue 3 (8th January 2020) - Kang, Hongwei; Zhang, Chengpeng; Xu, Yonggui; Zhang, Weiyang; Jiao, Jianhua; Li, Zhikun; Zhu, LeiLei; Liu, Xiaoqian
Abstract : Schematic illustration of the facile synthesis process of DAPrGOs nanocomposites, Ragone plots and the superior cyclic stability of the assembled DAPrGO1//DAPrGO1 SSS. Abstract : In this paper, novel reduced graphene oxide (rGO) composites (DAPrGOs) modified by diaminopyrene (DAP) were successfully synthesized via a facile solvothermal reaction method and used for supercapacitors. Compared with the pristine rGO, the DAPrGO1 electrode showed distinctly better performance (397.63 F g −1 vs. 80.29 F g −1 of pristine rGO at 0.5 A g −1 ) with small charge transfer resistance. When a symmetric device was fabricated using DAPrGO1 as the active material, it also exhibited a high capacitance of 82.70 F g −1 at 0.5 A g −1 with an energy density of 25.84 W h kg −1 at a power density of 375 W kg −1, and even offered a high power density of 7500 W kg −1 (18.71 W h kg −1 ) at 10 A g −1 . Moreover, the device possessed good electrochemical stability up to 20 000 cycles, implying promising applications in energy storage fields.